PENGARUH LATIHAN FISIK TERHADAP FREKUENSI DENYUT NADI - Sandi, I Nengah (Sport and Fitness Journal; Volume 4, No. 2, 2016)
Physical exercise leads to an increase on the pulse rate. This increase was due to increased needfor blood that transports O2 to the tissues of the body active, transporting waste material such asCO2 and other metabolic byproducts. Increasing the intensity of exercise, the exercise pulse rateincreases, on the contrary decreased intensity of exercise, the pulse rate decreases. These changesare regulated by the nervous system and the hormonal system. This is the acute effects ofexercise. If the physical exercise done regularly and continuously in the long term, there will bea decrease in the resting pulse rate. It is a chronic effect of exercise. This article aims to describethe effects of physical exercise on the pulse rate.
Keywords: physical exercise, pulse rate, acute effects of exercise, chronic effect of exercise